You are on page 1of 6

Homework Assignment 1 Solution Set

PHYCS 4420 23 January, 2004


Problem 1 a (Griths 1.11(b)) f (x, y, z) = x2 y 3 z 4 f = f f f x+ y+ z x y z = 2xy 3 z 4 x + 3x2 y 2 z 4 y + 4x2 y 3 z 3 z

b (Griths 1.15(c)) v(x, y, z) = y 2 x + (2xy + z 2 ) + 2yz z y vx vy vz + + x y z = 2x + 2y

v =

(Griths 1.18(c)) v(x, y, z) = y 2 x + (2xy + z 2 ) + 2yz z y vy vx vz vy vx vz ) + ( x ) + ( y ) z y z z x x y = (2z 2z) + (0 0) + (2y 2y) x y z = 0. f , where f = xy 2 + yz 2 .

v = (

Note: You may have recognized that v(x, y, z) = Thus, by Griths equation 1.44, v = 0. Problem 2 (Griths 1.12)

h(x, y) = 10(2xy 3x2 4y 2 18x + 28y + 12)

a The stationary points of h are found where peak we set h=0

h = 0. Thus, to nd the

(60x + 20y 180) + (80y + 20x + 280) = 0, x y which, of course, can only be true if 3x + y 9 = 0 and x 4y + 14 = 0. Solving this system of simultaneous equations gives only one solution at the point (2, 3); i.e., 3 miles north and 2 miles west of South Hadley. This position must correspond to the top of the hill. We know it is a maximum (rather than another type of stationary point) because of the form of h(x, y) (its quadratic, and the coecients of x2 and y 2 in h(x, y) are both negative). b h(2, 3) = 10(2(2)(3) 3(2)2 4(3)2 18(2) + 28(3) + 12 = 720f t c h(1, 1) = (60(1) + 20(1) 180) + (80(1) + 20(1) + 280) x y = 220 + 220 x y The slope of the hill is the magnitude of the gradient, which is 220 2f t./mile. It points uphill in the direction of the gradient, which is to the north-west. Problem 3 (Griths 1.21) a We should obey the parentheses and compute the product they contain rst. However, is an operator, so we should leave it open to act on the right as it is written. Thus, (A = (Ax )B = (Ax + Ay + Az )B x y z

Bx Bx Bx By By By Bz Bz Bz +Ay +Az )+(Ax x +Ay +Az )+(Ax y +Ay +Az ). z x y z x y z x y z

b r= x + y y + z z x x2 + y 2 + z 2

Since the functional form of r is identical for {x, y, z}, we need only compute one component of ( ) (the others will be the same with the variables simply r r interchanged). (( r ))x = rx r rx rx rx + ry + rz x y z y2 + z2 1 xy xz (x( = ) + z( )) 3 ) + y( 2 + y2 + z2 ) 2 2 + y2 + z2 ) 3 2 + y2 + z2 ) 3 2 + y2 + z2 2 2 (x (x (x x 1 (x(y 2 + z 2 ) xy 2 xz 2 ) = 2 (x + y 2 + z 2 )2 =0 ) = 0. r

Thus, ( r

Problem 4 (Griths 1.24(a) - optional) A = x + 2y y + 3z z x B = 3y 2x x y Wed like to prove product rule (iv) from the text, namely (A B) = B ( First, lets expand the left hand side: A B = (0 (6xz)) + (9yz 0) + (2x2 6y 2 ). x y z So, taking the divergence gives (A B) = 6z + 9z = 15z. Now for the right hand side. First well compute the curls: A = (0 0) + (0 0) + (0 0) = 0, x y z B = (0 0) + (0 0) + (2 3) = 5. x y z z So the right hand side is B( A) A ( B) = 0 3z(5) = 15z. A) A ( B).

Problem 5 (Griths 1.25) 3

b T (x, y, z) = sin x sin y sin z


2

T = sin x sin y sin z sin x sin y sin z sin x sin y sin z = 3T (x, y, z)

d v(x, y, z) = x2 x + 3xz 2 y 2xz z


2

v = ( 2 vx ) + ( x = 2 + 6x x y

vy ) + ( y

vz ) z

Problem 6 (Griths 1.31) T (x, y, z) = x2 + 4xy + 2yz 3 T = (2x + 4y) + (4x + 2z 3 ) + (6yz 2 ) x y z Wed like to prove that
b

( T ) dl = T (b) T (a)
a

regardless of the path we choose. First, lets nd the right hand side so we know what to look for on the left. T (b) T (a) = T (1, 1, 1) T (0, 0, 0) = (1)2 + 4(1)(1) + 2(1)(1)3 = 7 a (0, 0, 0) (1, 0, 0) (1, 1, 0) (1, 1, 1) Along this path we have three separate line integrals.
(1,1,1) 1 1 1

( T ) dl =
(0,0,0) 0 1

T dx x
y=0=z 1

+
0 1

T dy y
x=1,z=0

+
0

T dz z
x=1=y

=
0

2xdx +
0

4dy +
0

6z 2 dz

= 1+4+2=7

c (0, 0, 0) (1, 1, 1); z = y 2 , y = x Now we have three integrals for a dierent reason (sort of). Theres just one smooth path, but our path integral gets split into components. In each integral we substitute expressions for each variable in terms of the variable of integration.
(1,1,1) 1 1 1

( T ) dl =
(0,0,0) 0 1

(2x + 4y)dx +
0 1

(4x + 2z 3 )dy +
0 1

6yz 2 dz
5

=
0

6xdx +
0

(4y + 2y 6 )dy +
0

6z 2 dz

2 12 = 3 + (2 + ) + =7 7 7 Problem 7 (Griths 1.33) v(x, y, z) = xy + 2yz y + 3zx x z

Stokes Theorem says that (


S

v) dA =
P

v dl.

The right hand side of this equation is easy. Following the arrows in Figure 1.34, and starting from the origin, we have three line integrals:
2 0

vdl =
P 0

(xy+2yz y +3zx)dy y + x z
P

(xy+2yz y +3zx)(dy y +dz z )+ x z


2

(xy x+2yz y +3zx)(dz z ). z

The second line integral must be split into two integrals: one in the y-direction and one in the z-direction. Also, in each integral we should replace the nonintegrated variables with appropriate values. In the rst path we hold x = z = 0, so the integral vanishes. In the third path we have x = y = 0, so it also vanishes. However, in the second path we have x = 0 and z = 2 y. Thus,
2 0 2 0

v dl =
P 0 2

2yzdy +
2

2y(2 y)dy +
0

3zxdz +
2

3zx(dz)

=
0

(2y 2 4y)dy 16 8 8= . 3 3 5

For the left hand side of Stokes Theorem we note that the positive x direction is the direction of dA. This is given by the right hand rule according to the path we took above. Thus, we need to nd (
S

v) dA =
S

v) (dydz x),

where v = (0 2y) + (0 3z) + (0 x). x y z There are a few ways to proceed with the double integral from here. Lets integrate over z rst, since vx doesnt depend on z. The z boundary, however, depends on y. Thus,
2y 2

(
S

v) dA =
0 2 0

dzdy(2y 3z y x) x x z dy(2 y)(2y)


0

8 = . 3